– (Requirements for activating the investment in the Iraqi insurance company- Applied Study for the Period (2004- 2015 - Akkar, Zeinab Shallal; Sultan, Wafa Ali (Journal of Economic, Administrative and Legal Sciences, 2019)
The insurance sector is one of the most important sectors of the financial services in the world، and it keeps pace with all other economic activities and contributes to its support، development and stability. This study aims to review the investment in insurance companies and the revenues obtained from it، where insurance companies collect large amounts of premiums that enter and then invest in various areas in economic life، and in order to achieve appropriate returns to cover their obligations towards the policyholders and payment of compensation، Factors necessary for successful investment function in insurance companies.
Keywords: investment; insurance premiums; investment returns